Effect of magnetic field and gamma radiation on Paulowinia tomentosa tissue culture - Alikamanoğlu, Sema; Yaycılı, Orkun; Rzakoulieva, A.; ATAK, ÇİMEN (DIAGNOSIS PRESS LTD, 67 DONDUKOV BLVD, 1504 SOFIA, BULGARIA, 2007)
In this study Me in vitro tissue culture of the Paulownia tomentosa plant was established and a magnetic field which has 2.9-4.8mT flux density was applied to the culture at a velocity of 1m/s for 19.8 seconds. Additionally, gamma radiation of 10 and 25 Gy was applied as combined to the magnetic field. It was observed that magnetic field increased the capability of regeneration of Paulownia tomentosa cultures and supported the regeneration in a short time in comparison with the control group and applied radiation dose and decreased regeneration capability were re-supported when combined with magnetic field. It was found that magnetic field has a positive effect on plant fresh weight, leaf number and chlorophyll amount on the 28(th) day of established cultures Q P tomentosa node explants and the negative effects on these parameters by radiation, when magnetic field and gamma radiation applied together these parameters changed and aroused depending on the radiation doses.
Keywords: radiosensitivity; magnetic field; node culture; gamina rays; Paulownia; growth; L.; regeneration; germination; system; seeds; radyoduyarlılık; manyetik alan; düğüm kültürü; gamina ışınları; büyüme; yenilenme; çimlenme; sistem; tohumlar